The Influence Of Work Environment And Motivation On Employee Performance At Pt Catur Mitra Sejati Sentosa (Mitra 10 Siliwangi) Pamulang-South Tangerang - Prasetyo Kurniawan; Noto Susanto (Pasundan Social Science Development, 2026)
This study aims to determine the influence of the environment and work motivation on employee performance at PT Catur Mitra Sejati Sentosa (Mitra 10 Siliwangi) Pamulang-South Tangerang both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and obtained samples in this study amounting to 72 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, analysts correlation coefficient analysis, determination coefficient analysis and hypothesis test. The result of this study is that the environment has a positive and significant effect on employee performance with the regression equation Y = 9.990 + 0.816X1, the correlation value obtained is 0.783 meaning that the two variables have a strong level of relationship. The value of the coefficient of determination is 61.3%. Test the hypothesis obtained the value of t count > t table or (10,553 > 1,994). Thus H0 is rejected and H1 is accepted meaning this means that there is a significant influence of the environment on employee performance. Work motivation has a positive and significant effect on employee performance with the regression equation Y = 4.888 + 0.892X2, the correlation value is obtained at 0.890 meaning that the two variables have a very strong level of relationship. The value of the coefficient of determination is 79.2%. Test the hypothesis obtained the value of t count > t table or (16.331 > 1.994). Thus, H0 is rejected and H2 is accepted, meaning that there is a significant influence of work motivation on employee performance. Work environment and motivation simultaneously have a positive and significant effect on employee performance with the regression equation Y = 2.783 + 0.191X1 + 0.744X2, the correlation value or level of relationship between the independent variable and the dependent variable is obtained at 0.896 meaning that it has a relationship that is very powerful. The value of the coefficient of determination or contribution of influence simultaneously amounted to 80.4% while the remaining 19.6% was influenced by other factors. Test the hypothesis obtained the value of f count > f table or (141,256 > 3,130). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence of the environment and work motivation on employee performance.